Power Sector of Uzbekistan. Current situation and future conceivable energy market models - I.O.Ismoilova; Kh.R.Nuriddinova (Zien Journals, 2022)
The transformation of energy sector needs substantial changes in legal and regulatory framework; institutional structure and sector governance. This article covers and analyses main options and criteria which were chosen for Uzbekistan in order to find optimal way for transition period of reforming power sector
Keywords: Uzbekistan; energy sector; reforms; energy market; single buyer